Strategi Pemasaran Produk Olahan Ubi Jalar pada UMKM Sumber Makmur Kabupaten Sorong - Sitti Hadija Samual; Indra Irjani Dewijanti; Anggita Ekaningtyas Hermawan`; Aci Aprianto (Journal of Agribusiness, Social and Economic, 2026)
This study identifies and evaluates the marketing strategy of Sumber Makmur UMKM in marketing processed sweet potato products in Sorong Regency. A descriptive qualitative method was applied through observation, in-depth interviews, and documentation involving five purposively selected enterprise members. The data were analyzed using the 7P marketing mix and SWOT analysis. The results show that the enterprise is strengthened by quality local raw materials, a healthy product image, flavor variation, practical packaging, and affordable prices. Its main weaknesses are limited production capacity, uneven distribution, harvest-season dependence, and suboptimal digital promotion. Marketing strategy should therefore focus on production strengthening, digital promotion, wider distribution partnerships, and product differentiation